2016
DOI: 10.1016/j.bbamem.2016.07.016
|View full text |Cite
|
Sign up to set email alerts
|

R- and S-terbutaline activate large conductance and Ca 2+ dependent K + (BK Ca ) channel through interacting with β 2 and M receptor respectively

Abstract: This study investigated the effect of the β receptor agonist terbutaline on the single channel activity of BK channel. The effects of racemate and two isomers of terbutaline were all assessed. β adrenoceptors were stably overexpressed on HEK293 cells by lentiviral transduction method and chicken BK channels were transiently expressed on normal HEK293 cell line or HEK293 cells overexpressing β receptors. Data showed that terbutaline significantly increased the single channel open probability of BK channel withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…β 2 -adrenoceptor agonists via activation of β 2 ARs regulate necessary key proteins for the process of alveolar epithelial active Na + transport through activation and increase in expression of ion channels and reduce pulmonary endothelial permeability [ 31 , 32 , 33 , 34 , 35 , 36 ]. Ion channels which can be modulated by β 2 -adrenoceptor agonists by their activity or expression include epithelial sodium channel (ENaC) [ 21 , 36 , 37 ], Na + /K + -ATPase [ 30 , 38 , 39 , 40 , 41 ], cystic fibrosis transmembrane conductance regulator (CFTR) [ 42 ], cyclic nucleotide-gated cation (CNG) channels [ 21 ], nonselective cation channel (NSCCa) [ 43 ] and Ca 2+ dependent K + channel (BKCa) [ 44 , 45 ]. Moreover, treatment with β2-agonists increases the secretion of surfactant proteins and exerts anti-inflammatory properties by influencing several types of immune cells and reducing fibrotic remodelling [ 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…β 2 -adrenoceptor agonists via activation of β 2 ARs regulate necessary key proteins for the process of alveolar epithelial active Na + transport through activation and increase in expression of ion channels and reduce pulmonary endothelial permeability [ 31 , 32 , 33 , 34 , 35 , 36 ]. Ion channels which can be modulated by β 2 -adrenoceptor agonists by their activity or expression include epithelial sodium channel (ENaC) [ 21 , 36 , 37 ], Na + /K + -ATPase [ 30 , 38 , 39 , 40 , 41 ], cystic fibrosis transmembrane conductance regulator (CFTR) [ 42 ], cyclic nucleotide-gated cation (CNG) channels [ 21 ], nonselective cation channel (NSCCa) [ 43 ] and Ca 2+ dependent K + channel (BKCa) [ 44 , 45 ]. Moreover, treatment with β2-agonists increases the secretion of surfactant proteins and exerts anti-inflammatory properties by influencing several types of immune cells and reducing fibrotic remodelling [ 16 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that R ‐isomer of TBT was the potent part to generate the activity by stimulating β 2 ‐adrenoceptor, while the S ‐isomer had virtually no affinity for β 2 ‐adrenoceptor or was predominantly ascribable to the side effects, such as causing airway hyperreactivity and cardiac disorders . Recently, Zhuo Fan et al reported that, S ‐enantiomer of TBT may activate muscarinic receptors which could generate the airway hyperreactivity of racemic terbutaline . To date, much efforts have been devoted to produce R ‐TBT 5 , either by absolute asymmetric synthesis, or by chemo‐enzymatic method in which asymmetric reduction of a substituted α ‐chloroacetophenone derivative with cultured whole‐cell biocatalyst of yeast (Williopsis californica JCM 3600), or by catalytic asymmetric synthesis from chloroketones, or using chiral selector (β‐cyclodextrin or its derivatives) .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11] Recently, Zhuo Fan et al reported that, S-enantiomer of TBT may activate muscarinic receptors which could generate the airway hyperreactivity of racemic terbutaline. 12 To date, much efforts have been devoted to produce R-TBT 5, either by absolute asymmetric synthesis, 13 or by chemo-enzymatic method in which asymmetric reduction of a substituted α-chloroacetophenone derivative with cultured wholecell biocatalyst of yeast (Williopsis californica JCM 3600), 14 or by catalytic asymmetric synthesis from chloroketones, 15 or using chiral selector (β-cyclodextrin or its derivatives). [16][17][18][19] However, these methods couldn't achieve products with high optical purity for industrial application.…”
Section: Introductionmentioning
confidence: 99%